PENERAPAN UNDERGRAVEL AIRLIFT PUMP PADA AKUAKULTUR IKAN NILA (Oreochromis Sp) - Kurniawan Muhammad Nur; Halil Halil; Driyanto Wahyu Wicaksono (Jurnal Akuakultur Rawa Indonesia, 2020)
Undergravel airlift pump is a simple filter system that uses air. The purpose of this study was to analyze the efficiency of using Undergravel Airlift Pump in Aquaculture Oreochromis sp. The approach used is an experimental approach with 2 treatments and 1 control. Analysis of the data used is the analysis of variance (ANOVA). The results showed that the application of undergravel airlift pump had an impact on water quality. The treatment of middle airlift  position is more effective compared to the bottom airlift  and control. The temperature and pH parameters were not significantly different; dissolved oxygen and total dissolved solid were significantly different.